2019
DOI: 10.1002/cpe.5575
|View full text |Cite
|
Sign up to set email alerts
|

An improved energy‐low clustering hierarchy protocol based on ensemble algorithm

Abstract: Summary LEACH (low‐energy adaptive clustering hierarchy) protocol is an important part of wireless sensor network (WSN) and consisting of a good deal of energy‐constrained nodes. LEACH is widely used but also faces various challenges and constraints. The biggest constraint is that the energy is limited and the network life is finite. In the article, an improved ensemble algorithm based on energy‐efficient LEACH is proposed. The ensemble algorithm benefits from the cuckoo search algorithm (CS), glowworm swarm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Xie et al [11] developed an improved hierarchy protocol for low-energy clustering based on the ensemble method. is work primarily optimizes and enhances the LEACH protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xie et al [11] developed an improved hierarchy protocol for low-energy clustering based on the ensemble method. is work primarily optimizes and enhances the LEACH protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose was to take into account the distance of residual energy from the cluster's average well and the CH equilibrium constant. PenghuaXie et al [14] concluded that the LEACH protocol is an integral part is often used, but it also presents many challenges and limitations. The main limitation is that performance and network lifespan is limited.…”
Section: Literature Surveymentioning
confidence: 99%
“…The general premise of cluster routing protocols is to lower the amount of CH data transmissions. LEACH was merged the undisputed access of TDMA with the cluster concept in WSN and proposed a cluster route algorithm [14]. The critical problem in LEACH routing WSN is the effective energy consumption [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's practical applications necessitate improving positioning accuracy, cost efficiency, and power consumption. However, developing a lowenergy, accurate, stable, and functional algorithm is difficult [4]. A typical WSN comprises hundreds of small, self-contained sensor nodes with limited battery capacity.…”
Section: Introductionmentioning
confidence: 99%